Study of Nitrification Process in a Media Raised Bed Based Aquaponic System - Prasetiawan, Haniif; Aulia Mukadis; Afrissa Viola Motti; Nurhayati; budi setiawan (Journal of Clean Technology, 2024)
Aquaponics is an integrated and sustainable farming method that combines aquaculture and hydroponics in a recirculating water system. This system utilizes fish waste as a nutrient source for plants, and the plants act as biofilters to clean the water before it returns to the fish tank. A critical process in this system is nitrification, where ammonia is converted into nitrite and nitrate by beneficial bacteria, reducing toxicity to fish and providing nutrients for plants. This study investigates the efficiency of the nitrification process using four different biofilter media—rockwool, pumice stone, gravel, and zeolite—in a media-raised bed aquaponic system. Results showed that pumice stone provided the highest nitrate concentration (131.62 mg/L), indicating superior nitrification performance. The findings offer valuable insights for optimizing biofilter media selection in aquaponic systems, which is crucial not only for maintaining water quality but also for enhancing crop productivity. The study contributes to the development of more efficient and sustainable aquaponic designs, particularly in regions facing water scarcity and the need for integrated food production solutions.